Insights into the mechanics of solid conical microneedle array insertion into skin using the finite element method. (November 2021) - Shu, Wenting; Heimark, Helen; Bertollo, Nicky; Tobin, Desmond J.; O'Cearbhaill, Eoin D.; Annaidh, Aisling Ní
Abstract: In order to develop optimum microneedle designs, researchers must first develop robust, repeatable and adaptable test methods which are representative of in vivo conditions. However, there is a lack of experimental tools which can accurately comparatively interrogate functional microneedle penetration of tissue. In this study, we seek to develop a state of the art finite element model of microneedle insertion into and penetration of human skin. The developed model employs a 3D hyperelastic, anisotropic pre-stressed multi-layered material which more accurately reflects in vivo skin conditions, while the microneedle is modeled as an array, which can capture the influence of adjacent microneedles on the overall response. Using the developed finite element model, we highlight the importance of accurate computational modeling which can decipher the mechanics of microneedle insertion, including the influence of its position within an array and how it correlates well with experimental observations. In particular, we have concluded that, for our model microneedle array, increasing skin pretension from 0 to 10% strain reduces the penetration force by 13%, ultimate local deformation about the microneedle by 22% and the ultimate penetration efficiency by 15%. We have also concluded that the presence of a base plate limits the penetration efficiency by up to 24%, while the penetration efficiency across a 5 × 1 microneedle array may vary by 27%. This model elucidates, for the first time, the combined effects of skin tension and needle geometry on accurately predicting microneedle penetration efficiency. Statement of Significance: Microneedles arrays (MNAs) are medical devices with microscale protrusions, typically designed to penetrate the outermost layer of the skin, that upon optimisation, could lead to disruptive minimally-invasive disease management. However, the mechanics of MNA insertion are complex, due in part to a 'bed of nails' effect, and difficult to elucidate experimentally. Therefore, comparisons between designs, functional assessment of production batches and ultimately the likelihood of clinical translation are challenging to predict. Here, we have develop the most sophisticated in silico model of MNA insertion into pre-tensioned human skin to predict the extent of MNA penetration and therefore the likelihood of successful therapeutic delivery. Researchers can customise this model to predict the penetration efficiency of any MNA design. Graphical abstract: Image, graphical abstract